1999
DOI: 10.5089/9781451851632.001
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating Tariff Reduction and Domestic Tax Reform

Abstract: A key obstacle to fundamental tariff reform in many developing countries is the revenue loss that it ultimately implies. This paper establishes a simple and practicable strategy for realizing the efficiency gains from tariff reform without reducing public revenues, showing that for a small open economy, a cut in tariffs combined with a point-for-point increase in domestic consumption taxes increases both welfare and public revenues. Increasingly stringent conditions are required, however, to ensure unambiguous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…However, since the inception of World Trade Organization (WTO) in 1995, both developed and developing countries have experienced a significant degree of liberalisation of their trade regimes, which has presumably led to a decline in international trade tax revenue and hence a fall in public revenue. A number of studies have reported empirical evidence or emphasised the public revenue losses associated with greater trade liberalisation (or trade openness) (Baunsgaard & Keen, ; Berg & Krueger, ; Bevan, ; Cagé & Gadenne, ; Castanheira, Nicodème, & Profeta, ; Crivelli, ; Greenaway & Milner, ; Hisali, ; Keen & Ligthart, ; Keen & Simone, ; Khattry & Rao, ; Longoni, ; Moller, ; Waglé, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, since the inception of World Trade Organization (WTO) in 1995, both developed and developing countries have experienced a significant degree of liberalisation of their trade regimes, which has presumably led to a decline in international trade tax revenue and hence a fall in public revenue. A number of studies have reported empirical evidence or emphasised the public revenue losses associated with greater trade liberalisation (or trade openness) (Baunsgaard & Keen, ; Berg & Krueger, ; Bevan, ; Cagé & Gadenne, ; Castanheira, Nicodème, & Profeta, ; Crivelli, ; Greenaway & Milner, ; Hisali, ; Keen & Ligthart, ; Keen & Simone, ; Khattry & Rao, ; Longoni, ; Moller, ; Waglé, ).…”
Section: Introductionmentioning
confidence: 99%
“…VAT is therefore less susceptible to evasion than a retail sales tax, for which collection occurs during the final stage of production. The recent empirical evidences point to a positive effect of VAT adoption on revenue performance in developing countries (Gordon & Nielsen, ; Auriol & Warlters, ; Michael et al ., ; Hatzipanayotou et al ., ; Abe, ; Keen & Ligthart, ; Keen & Lockwood, ).…”
Section: Introductionmentioning
confidence: 99%
“…(), for instance, show theoretically that not only welfare but also revenues increase, as long as a uniform reduction in trade taxes is combined with increases in consumption taxes that keep consumer prices constant. Building further on these findings, Keen and Ligthart () prove that the same result is achieved under any tariff reduction, provided that the latter increases the value of domestic production at world prices. In the presence of a shadow economy however, the usefulness of a consumption‐based tax is undermined in Emran and Stiglitz (), who demonstrate that successful substitution between trade and consumption taxes may not occur when the size of hidden activities is high enough to leave part of the final consumption untaxed.…”
Section: Introductionmentioning
confidence: 89%